The effect of obesity on inflammatory cytokine and leptin production following acute mental stress. (29th October 2015) - Caslin, H. L.; Franco, R. L.; Crabb, E. B.; Huang, C. J.; Bowen, M. K.; Acevedo, E. O.
Abstract: Obesity may contribute to cardiovascular disease (CVD) risk by eliciting chronic systemic inflammation and impairing the immune response to additional stressors. There has been little assessment of the effect of obesity on psychological stress, an independent risk factor for CVD. Therefore, it was of interest to examine interleukin‐6, tumor necrosis factor‐α, interleukin‐1β (IL‐1β), interleukin‐1 receptor antagonist (IL‐1Ra), and leptin following an acute mental stress task in nonobese and obese males. Twenty college‐aged males (21.3 ± 0.56 years) volunteered to participate in a 20‐min Stroop color‐word and mirror‐tracing task. Subjects were recruited for obese (body mass index: BMI > 30) and nonobese (BMI < 25) groups, and blood samples were collected for enzyme‐linked immunosorbent assay analysis. The acute mental stress task elicited an increase in heart rate, catecholamines, and IL‐1β in all subjects. Additionally, acute mental stress increased cortisol concentrations in the nonobese group. There was a significant reduction in leptin in obese subjects 30 min posttask compared with a decrease in nonobese subjects 120 min posttask. Interestingly, the relationship between the percent change in leptin and IL‐1Ra at 120 min posttask in response to an acute mental stress task was only observed in nonobese individuals. This is the first study to suggest that adiposity in males may impact leptin and inflammatory signaling mechanisms following acute mental stress.